Equilibrium configurations for carbon nano-stacked cups - Duangkamon Baowan (2018)
Nano-stacked cups comprise truncated nanocones such that the cone vertices have been shortened, and they can be found as the core in nanofibers. The stacked cups are candidates for many novel nanoelectronic applications due to the high curvature of the truncated cone vertices which generate a large exposed and reactive area. From experiments, the cup angles measured from the fiber axis vary from 10° to 80°, and sometimes they can be observed as a nested set of cups. In this paper, we investigate the molecular interaction energy between two carbon stacked cups utilizing the Lennard-Jones potential function and the continuous approximation. The equilibrium position (spacing) between two cups in the axial direction is obtained by minimizing the total molecular energy of the system using s numerical calculation. Further, analytical expressions are presented in terms of hypergeometric functions which may be rapidly evaluated. Numerical results indicate good overall agreement with known experimental structures. Copyright © 2011 American Scientific Publishers.